Synthesis of reference standards to enable single cell metabolomic studies of tetramethylrhodamine-labelled ganglioside GM1 - Larsson, E. Andreas (2006)
Ganglioside GM1 and its seven potential catabolic products: asialo-GM1, GM2, asialo-GM2, GM3, Lac-Cer, Glc-Cer and Cer, were labelled with tetramethylrhodamine (TMR) to permit ultra-sensitive analysis using laser-induced fluorescence (LIF) detection. The preparation involved acylation of the homogenous C18 lyso-forms of GM1, Lac-Cer, Glc-Cer and Cer with the N-hydroxysuccinimide ester of a β-alanine-tethered 6-TMR derivative, followed by conversion of these labelled products using galactosidase, sialidase and sialyltransferase enzymes. The TMR-glycolipd analogs produced are detectable on TLC down to the 1 ng level by naked eye. All 8 compounds could be separated in under 4 minutes in capillary electrophoresis where they could be detected at the zeptomole (ca 1000 molecule) level using LIF.